Vínculo afectivo de la profesional de enfermería por su condición de mujer y madre en el cuidado a niños hospitalizados. Hospital Alfredo Noboa Montenegro año 2021. - Carvajal Analuiza, Andrea Patricia (2021)
The research topic on epidemiological characterization of people with physical disabilities aged 36-64 years who attend the Gonzalo Cordero Crespo Health Center in the city of Guaranda in the period December 2020- May 2021, three specific objectives were established; identify the causes of physical disability, recognize the level of severity of physical disability and diseases that the priority group has, develop a support instrument (guide) with clear guidelines for comprehensive care for people with physical disabilities focused on healthy habits with in order to minimize at least part of the risk factors. Through the descriptive methodology of a cross-sectional study, the epidemiological characteristics of a sample of 82 people were identified and described, which was carried out through the review of the patient's medical records, the only document of the patient and a survey applied in each home, verifying that 22 multiple-choice questions, for further processing and analysis of results in Microsoft Word and Microsoft Excel software. The research gave us the main epidemiological characteristics of the 82 users with physical disabilities as follows: regarding distribution according to gender, we have 42 men who represent 51% and 40 women who reflect 49% of the total number of people In the study, in relation to age we have that the highest percentage of physical disability is centered in the age group of 54 years and over with 45 people that represents 55%, followed by the ages of 45 to 53 years with 24 people that reflects 29% and finally the group from 36 to 44 years old has 13 people, which corresponds to 16%. In relation to the place of residence, 69 people, which represents 84%, live in the urban sector, while 13 users, which is 16%, reside in rural areas, regarding the level of instruction of the study group, 56 people, which is 68%, reached primary school, followed by 12 people, which corresponds to 15%, managed to complete secondary school, while 10 people, which concerns 12%, passed the third level of study and finally only 4 people, which is 5%, reached the fourth level, which is the same with greater development and opportunities in society. Physical disability can be acquired or suffered at any stage of life, adulthood being more predictable because it is an economically active population and is immersed in society, as evidenced in our study that 59 people, representing 72%, acquired the physical disability in adulthood, followed by 12 that reflects the 15% obtained at birth, while 9 that represents 11% corresponds to the stage of adolescence and finally 2 that represents 2% acquired in childhood. At the end of the degree project, it is concluded that the causes of physical disability in the study group are produced to a greater extent by traffic accidents with 20 people, which is 24%, followed by some diseases subdivided as follows: 13 people su Disability was the product of chronic degenerative diseases that reflects 16%, 24 individuals that correspond to 30% was caused by genetic factors and domestic accidents, while 20 that reflects 24% was caused by catastrophic and viral diseases, work accidents 3 people who symbolize 4% and finally 2 users that correspond to 2% occurred due to violence that was the product of fights caused in the street. Physical disability is a consequence of a neuromusculoskeletal deficiency or of the organs, causing incoordination of movement and balance, so 46 people, which is 56%, present limitation at the level of the lower limbs, while 11 people, which is 13%, their affectation is in the head, followed by 9 people who represent 11% of the upper limbs and finally 16 people who represent 20% have trunk level involvement and organ XXI damage. Regarding the generic scale of severity stipulated by the Ministry of Public Health, moderate disability corresponding to 25-49%, in our study is the most prevalent, consisting of 40 people who represent 49%, being those independent in overcoming barriers of the environment, while 27 people, which represents 33%, have a severe disability and 14, which reflects 17%, belong to a very serious disability and finally 1 person has a complete disability, which is 96-100%, representing 1% the same that makes it impossible for them to perform activities of daily life. In relation to technical aids used by some people with physical disabilities, it was possible to identify that 61 people, which is 74%, do not require any technical help despite their disability limitation, while 11 users representing 13% use canes or crutches, followed of 6 individuals, 7% have wheelchairs, followed by 3, 4% have walkers for their respective movement, and finally 1 person, representing 1%, uses a prosthesis at the right hip level. Regarding amputations, according to the research carried out, 77 people, representing 94%, do not show any type of amputation, while a minority of 5, which is 6%, have some amputation, mainly in the upper and lower limbs. In relation to medical care, 43 people, that is, 53% attend the establishments of the Ministry of Public Health for their medical checks, 28 people, which is 34%, attend the Ecuadorian Institute of Social Security, 8 people who represent 10% go to entities private health workers and 3 people representing 4% go to the Police Social Security Institute. Of the 82 users with physical disabilities, 46 people, which is 56%, do not have any disease while 36, which is 39%, have comorbidities subdivided as follows: 12 with obesity, which is 15%, followed by overweight, which is 10 and represents 12%, thus there are 7 with hypertension that symbolizes 9%, while with depression there are 3 users that is 4%, followed by diabetes mellitus that 2 people have, which is 2%, and finally hypothyroidism and bedsores which represents 2%. According to medical controls, 66 users, representing 80%, XXII mention that their comorbidity is not under medical control, for fear of going out to be infected by the pandemic from which they opt for other measures, meaning that it is not necessary because not leads to greater damage while 16 people, which is 20%, go to medical appointments for check-ups and controls of their pathology, being at the same time in this group that 7 people consume losartan for their hypertension, 2 acquire glucocid, 1 take levothyroxine, while that 2 are in psychological therapy, 3 in nutritional treatments to improve their life habits and finally 1 person uses a moisturizing cream for bedsores. Regarding the frequency of medical check-ups carried out, 25 people, which is 30%, carry out their annual check-ups, followed by 23, which represents 28%, attend every six months, while 18, which is 22%, carry out their monthly check-ups and finally 16 people representing 20% attend quarterly. In relation to daily food, 67 people, 82%, eat three times a day, while 11, which represents 13%, buy food four times a day and finally 4 people, 5%, eat only twice a day . Regarding healthy eating habits, most people with physical disabilities consume food in a balanced way, which represents 44 people, that is, 54%, while 17 people consume foods rich in carbohydrates, representing 21%, 11 people who reflect the 13% consume protein, 7 people, which is 9%, consume fruits and vegetables and only 3 people, who represent 4%, consume fast food. Regarding physical activity, 44 people, representing 54%, rarely perform physical activity, 33 people, who reflect 40%, never do it, and only 5 people, which is 6%, always perform physical activity. People with physical disabilities according to care dependency, 62 people representing 76% mention that they do not require the help of a caregiver, while 20 people, 24% receive support and care from their direct relatives. According to the work environment in which they work, 55 people, which is 67%, are independent of their own work such as businesses, while 10 people representing 12% are retired and 9 users work in the public environment and finally 8, which is 10%, XXIII belong to the private sector. The state provides economic support to people with disabilities greater than 60%, of their disability and depending on the economic status to which they belong, so in the research carried out it was evidenced that 69 people, which is 84%, lack economic aid despite at their level of disability, while 6 people, which is 7%, have the human development bonus, followed by 4 people who represent 5% are beneficiaries of the José Joaquín Gallegos Lara bonus and finally 3 people who represent 4% They receive a contingency bonus for a health emergency (covid). Keywords: Physical disability, characterization, epidemiology, patient, support.